Gangguan Berbicara Akibat Faktor Lingual Pada Penderita Cadel (Kajian Psikolinguistik) - Rupa, Josephina Nirma; Dhapa, Dominika (Program Studi Pendidika Bahasa dan Sastra Indonesia, 2021)
This study aims to find and describe speech disorders due to lingual factors in people with lisp in psycholinguistic studies. This research approach uses a qualitative approach. As a key instrument, researchers carry out a series of research processes starting from planning research data, collecting data, analyzing data, interpreting, explaining the meaning of data, and concluding research results. In collecting data in this study, researchers used observation techniques and field notes. The analysis carried out in this study is (1) data collection, (2) data reduction, (3) data presentation, and (4) drawing conclusions. The theory used in this research is psycholinguistic theory. The results showed that problems in the relationship with speech disorders due to lingual factors in slurred sufferers, among others; in general, the result is due to oral structure, dysarthria, apraxia, bad habits as a child. There are factors that cause it, including: 1) Short speech organs such as the tongue, 2) Exposed to canker sores, and 3) Lack of parental awareness. In addition, there are also other factors that cause a person to become slurred, including: 1) lack of maturation of lip and tongue coordination, 2) physiological abnormalities in the form of hearing disorders, brain disorders, and disorders in the mouth region, 3) environmental factors, and 4) guides the child to recite the correct speech. Solutions to overcome speech disorders due to lingual factors in slurred sufferers, among others; 1) Practice two-way communication with children, 2) Play simple games with children, 3) Invite children to learn to sing together, 4) Get used to pronouncing the letter